39.7k views
1 vote
In the above triangle, if x = , y = 1, and z = 2, then which of the following is equal to tan(60°)?

A.
√(3)
B.
(√(2) )/(2)
C.
(√(3) )/(2)
D.
(√(3) )/(3)

In the above triangle, if x = , y = 1, and z = 2, then which of the following is equal-example-1

2 Answers

3 votes

Hello!

The answer is:

The correct option is:

A.
√(3)

Why?

Since we already know the hypothenuse and the opposite side of the triangle (y), we can calculate the value of "x" using the Pythagorean Theorem.

We have that:


Hypothenuse^(2)=Adjacent^(2)+Opposite^(2)

We know that:


Hypothenuse=z=2\\Adjacent=x=1

So, substituting and calculating we have:


2^(2)=1^(2)+Opposite^(2)


4-1=Opposite^(2)


Opposite^(2)=3\\Opposite=√(3)

Then,using the following trigonometric relation:


Tan(\alpha)=(Opposite)/(Adjacent)\\\\Tan(60\°)=Tan((Opposite)/(Adjacent))=Tan((√(3) )/(1))^=\sqrt{3

We have that the correct option is:

A.
√(3)

Have a nice day!

User Superkhau
by
4.8k points
3 votes

Answer: Option A


tan(60\°) = √(3)

Explanation:

We know the sides and z. So since it is a straight triangle we use the Pythagorean theorem to pull the length of the x side.


z ^ 2 = x ^ 2 + y ^ 2\\\\x^2 = z^2 - y^2\\\\x=√(z^2 - y^2)\\\\x=√(2^2 - 1^2)\\\\x=√(4 - 1)\\\\x=√(3)

By definition, the tangent of an angle is:


tan(\theta) = (opposite)/(adjacent)

In this case:


adjacent = y=1\\\\opposite=x =√(3)\\\\\theta=60\°

Then:


tan(60\°) = (√(3))/(1)


tan(60\°) = √(3)

User Axbeit
by
5.6k points